Absorptive capacity and the impact of commodity terms of trade shocks in resource export-dependent economies - Akiko Terada-Hagiwara; Mai Lin C. Villaruel; Christopher Edmonds (Asian Development Bank (ADB), 2016)
This paper investigates the role of 'absorptive capacity' to manage unexpected shocks to their real economy, with a focus on small, open, natural resource-dependent economies. A quarterly panel data series for 45 countries is constructed, including 23 developing Asian countries for empirical investigation. For the entire sample, the analysis finds that absorptive capacity, choice of exchange rate regime, presence of wealth funds, level of foreign reserves, or degree of resource dependency alone, does not matter when real shocks are introduced to output. However, levels of absorptive capacity or ability to use resource windfalls effectively, and foreign reserves begin to matter when the sample is restricted to resource-dependent countries. Case studies from Papua New Guinea and Timor-Leste support this claim highlighting the challenges they face with a sudden influx of natural resource revenues when capacity to effectively use fiscal revenues is limited.
Keywords: F14; F43; H11; 330; absorptive capacity; economic growth; natural resources; real exchange rate; terms of trade